Factors that Influence the Self-Efficacy of Former Drug Addicts to Stop Using Drugs: A Scooping Review - Mohamad Fikriyanto H. Kilo; Megah Andriany; Nur Setiawati Dewi (GLOBAL HEALTH SCIENCE GROUP, 2025)
A common problem among ex-drug users is relapse. Addiction in former drug users can be caused by self efficacy factors. This study aims to get a clear picture of the factors that influence the self-efficacy of former drug addicts to stop using drugs. Methods: Researchers used the scoping review method. The literature search was conducted using the search keywords